Review of Daniel Albright. 2000. Untwisting the Serpent: Modernism in Music, Literature, and Other Arts. Chicago: University of Chicago Press - Longobardi, Ruth (Current Musicology, 2002)
In their introduction to Modernism: 1890-1930, Malcolm Bradbury and James McFarlane acknowledge the inevitable limitations of studies on early twentieth-century literature: "Perhaps the most any account can offer," they warn, "is a personal or at least partial version of an overwhelmingly com-plex phenomenon, an individual selection from the infinity of detail" (1991:21). Numerous other scholars have shared the conviction that Mod-ernism should not be fixed within definitive parameters. The literary critic Linda Hutcheon, for example, describes the term Modernism as "a cultur-ally limited and limiting label" (1980:2-3; italics in the original). Art histo-rian Richard Sheppard devotes a chapter of his book on the European avant-garde to the problem of defining Modernism, which he understands as "a deeply and multiply fissured movement" (2000:5-6). And Jonathan Kramer warns against such reductions as "modernist vs. postmodernist" in the field of music. "Artistic movements," he argues, "refuse to be reduced out of existence by critics who draw arbitrary distinctions" (1984:345).